Evaluation of Salud Para Su Corazón (Health for Your Heart) - National Council of La Raza Promotora Outreach Program - Héctor Balcázar, PhD; Matilde Alvarado, RN, MSN; Mary Luna Hollen, PhD, RD; Yanira Gonzalez-Cruz, MPH; Verónica Pedregón (Centers for Disease Control and Prevention, 2005)
Introduction In 2001, the National Heart, Lung, and Blood Institute partnered with the National Council of La Raza to conduct a pilot test of its community-based outreach program Salud Para Su Corazón (Health for Your Heart), which aims to reduce the burden of morbidity and mortality associated with cardiovascular disease among Latinos. Methods The effectiveness of promotores de salud (community health workers) in improving heart-healthy behaviors among Latino families participating in the pilot program at seven sites was evaluated. Data on the characteristics of the promotores in the Salud Para Su Corazón program were compiled. Promotores collected data on family risk factors, health habits, referrals and screenings, information sharing, and program satisfaction from 223 participating Latino families (320 individual family members) through questionnaires. Paired t tests and chi-square tests were used to measure pretest-posttest differences among program participants. Results Results demonstrated the effectiveness of the promotora model in improving heart-healthy behaviors, promoting community referrals and screenings, enhancing information sharing beyond families, and satisfying participants' expectations of the program. The main outcome of interest was the change in heart-healthy behaviors among families. Conclusion The community outreach model worked well in the seven pilot programs because of the successes of the promotores and the support of the community-based organizations. Successes stemmed in part from the train-the-trainer approach. Promotoria, as implemented in this program, has the potential to be integrated with a medical model of patient care for primary, secondary, and tertiary prevention.